PENGARUH ELECTRONIC WORD OF MOUTH (E-WOM) DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK IMMUNOMODULATOR (PENELITIAN DI WILAYAH DKI JAKARTA) - Maulina, Novia; Sampurno, Sampurno; Andayani, Nurita; Laksmitawati, Dian Ratih (Jurnal Farmasi Indonesia, 2019)
Top Brand Index data during 2012-2018 shows a stagnant and prone to declining growth percentage for certain immunomodulatory products. Toovercome this problem, producers tried to promote their products vigorously and to apply the right marketing strategy of the electronic word of mouth (e-WOM). Moreover, strengthening brand image on purchasing decision could be an alternative way to increase the market share of immunomodulatory producer companies. Hence, this study aimed (1) to determine the effect of e-WOM toward the decision to purchase immunomodulator products (research conducted in the DKI Jakarta area) as well as (2) the brand image to the same matter, then (3) to investigate further to what extent e-WOM as a marketing strategy influence the brand image of the marketed product. This study used a survey method and questionnaires has been distributed to 384 respondents in DKI Jakarta area. The obtained data were then analysed using Structural Equation Modeling (SEM)-PLS (Partial Least Square) by means of SmartPLS software. The results showed that (1) e-WOM affects significantly toward the decision to purchase immunomodulatory products and so does (2) the brand image. Then, (3) e-WOM proved to have a significant effect on the brand image of immunomodulatory products.